POTENSI Aneurinibacillus thermoaerophilus STRAIN N25 DALAM PRODUKSI BIOLISTRIK PADA VARIASI STARTER - Echy Dania Putri; Irdawati; Azwir Anhar; Moralita Chatri (Universitas Cokroaminoto Palopo, 2026)
The development of renewable energy sources is important due to the increasing demand for electricity. Microbial Fuel Cell (MFC) is a technology that utilizes microorganisms to convert organic substrates into electrical energy. This study aims to determine the potential of Aneurinibacillus thermoaerophilus strain N25 in producing bioelectricity at different starter concentrations. The research was conducted using an experimental method with variations of starter concentrations in an MFC system. Bioelectricity production was measured using a digital multimeter in millivolts (mV). The results are expected to provide information about the optimal starter concentration for bioelectricity production by thermophilic bacteria.